2000
DOI: 10.1159/000014247
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Feeding Colostrum and a Formula with Nutrient Contents as Colostrum on Metabolic and Endocrine Traits in Neonatal Calves

Abstract: Colostrum provides high amounts of nutrients and non-nutrient substances to neonates. To study differences between effects of nutritional and non-nutritional components on growth, health status and metabolic and endocrine traits, a formula was created based on bovine milk components which contained similar amounts of nutrients as bovine colostrum during the first 3 days of lactation, but only trace amounts of growth factors (such as insulin-like growth factor I) or hormones (such as insulin) in whey. Calves we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

30
65
0
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(101 citation statements)
references
References 31 publications
(88 reference statements)
30
65
0
6
Order By: Relevance
“…As a consequence, the maturation of the postnatal somatotropic axis is delayed and leptin status is reduced in calves with insufficient colostrum supply (Hammon and Blum, 1997;Sauter et al, 2003;Blum et al, 2005). In the present study, we observed reduced plasma concentrations of IGF-I, leptin, T 3 , and T 4 as well as reduced plasma insulin, but elevated plasma cortisol concentrations, as was shown in other experiments (Hammon and Blum, 1998;Rauprich et al, 2000;Steinhoff-Wagner et al, 2011a), indicating an impaired energy status in calves fed no colostrum but a milk replacer with comparable energy content (Brockman and Laarveld, 1986;Hammon et al, 2012Hammon et al, , 2013. Greater plasma concentrations of leptin may point to larger fat depots in colostrum-fed calves (Reidy and Weber, 2000;Ingvartsen and Boisclair, 2001;Blum et al, 2005) and greater IGF-I plasma concentrations accentuate stimulation of anabolic processes in calves after feeding colostrum (Hammon and Blum, 1997;Sauter et al, 2003;Hammon et al, 2012).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…As a consequence, the maturation of the postnatal somatotropic axis is delayed and leptin status is reduced in calves with insufficient colostrum supply (Hammon and Blum, 1997;Sauter et al, 2003;Blum et al, 2005). In the present study, we observed reduced plasma concentrations of IGF-I, leptin, T 3 , and T 4 as well as reduced plasma insulin, but elevated plasma cortisol concentrations, as was shown in other experiments (Hammon and Blum, 1998;Rauprich et al, 2000;Steinhoff-Wagner et al, 2011a), indicating an impaired energy status in calves fed no colostrum but a milk replacer with comparable energy content (Brockman and Laarveld, 1986;Hammon et al, 2012Hammon et al, , 2013. Greater plasma concentrations of leptin may point to larger fat depots in colostrum-fed calves (Reidy and Weber, 2000;Ingvartsen and Boisclair, 2001;Blum et al, 2005) and greater IGF-I plasma concentrations accentuate stimulation of anabolic processes in calves after feeding colostrum (Hammon and Blum, 1997;Sauter et al, 2003;Hammon et al, 2012).…”
Section: Discussionsupporting
confidence: 88%
“…There is an obvious lack of promoting postnatal growth and maturation in calves fed milk with the same nutrient content as colostrum but no bioactive factors, such as growth factors, hormones, cytokines, and other peptides that support postnatal development and maturation (Blum, 2006;Gauthier et al, 2006;Blum and Baumrucker, 2008). The huge increase in plasma triacylglyceride concentrations in FF calves on d 4 was surprising, because fat intake was the same between groups, in contrast to previous findings where plasma triacylglycerides increased much more after colostrum than formula feeding (Rauprich et al, 2000;Hammon et al, 2012). However, fat in the present formula was from vegetable fat and based on palm and coconut oil, whereas in previous studies, milk …”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…It must be mentioned that colostrum and milk feeding influence glucose homeostasis in calves (Hammon and Blum, 1998;Rauprich et al, 2000). Since colostrum, milk, starter and roughage feeding management was constant among calves and all tests were carried out after a 14 h fast, confounding of the data by nutritional differences in the calves seems unlikely.…”
Section: Discussionmentioning
confidence: 99%